Development of Interactive Media Based on the STEAM Approach Through the NEARPOD Application to Improve Literacy Skills of Elementary School Students - Feri Novriadi; Yanti Fitria; Syafri Ahmad; Alwen Bentri (Jurnal Pendidikan Terapan, 2026)
Purpose: The low reading ability of elementary school students continues to be a problem in education. This condition is influenced by the ineffective use of technology-based interactive learning resources and the limited use of digital multimedia in the educational process. This project aims to provide interactive learning resources based on the Nearpod application with a STEAM approach to improve students' reading skills in science lessons in elementary schools. Methods: The preliminary research, prototyping phase, and assessment phase form the Plomp model, which was used in this research and development (R&D) study. All fifth-grade students and a small pilot group of three fifth-grade students participated in the study at SDN 20 Gumarang. Data collection methods included tests, questionnaires, interviews, and observations. Validity, practicality, and effectiveness tests using pretests, posttests, and N-Gain were used to analyze the data. This study was limited to a small sample size and focused solely on reading ability. Findings: The results of the study showed that Nearpod-based learning materials had a very high level of validity, with a percentage of material experts of 83.87%, a percentage of media experts of 91.67%, and a percentage of language experts of 91.67%. The media was also classified as very practical based on comments from students (88.75%) and instructors (94.28%). With an N-Gain score of 0.63 in the moderate category and an increase in the average pretest score from 58.35 to 84.50 on the posttest, students' reading ability also improved as a result of the learning materials. Research Implications: Through active, interactive, and student-centered learning, this study advances the creation of cutting-edge STEAM-based digital learning materials that enhance students' literacy skills. Originality: In contrast to other studies that only use Nearpod as an interactive media without STEAM integration, the uniqueness of this study lies in the integration of the STEAM method in creating Nearpod media for science learning to improve the reading skills of elementary school children.